Prática docente no ensino de Teatro: de que aula de Arte estamos falando? - Vissicchio, Thacio Fagundes (2022)
The present dissertation is bound by the Postgraduate Program of Masters in Arts, Prof-Artes, at the Federal University of Uberlândia, in the research line of Theoretical-Methodological approach of teaching practices.The central issue of this paper is the teaching of Theater at school and it aimed to understand and to introduce Theater from Drama as a schooling approach, in the curricular practice of Art class at Escola Estadual São José Operário, with students of 8th grade B, elementary school, final years, in the city of Rondonópolis, Mato Grosso. The research attempts to answer and reflect on the questions: how to develop Theater teaching through Drama based on the regulatory documents Common National Curricular Base and Curricular Reference Document of Mato Grosso? Do the regulatory documents contribute to Theater teaching in schools? How to transform classroom into a space for theatrical creation and experimentation without considering theater as a workshop or something disparate from school. The methodology of this investigation was: bibliographic survey on the researched areas (Theater Pedagogy, Educational Policies and Drama); document analysis on the National Curricular Common Base and Curriculum Reference Document of Mato Grosso; elaboration of a Drama process from the aforementioned documents. As a result, the drama Be kind, carried out with the students, is presented. Also, the analyzes and discussions that based this practice, which pervades the normative and generalizing documents, creating the possibility of resistance of theater in the classroom from Drama as an educational approach.